Inflammatory pathways and anti‐inflammatory therapies in sickle cell disease - Karina Tozatto‐Maio; Felipe A. Rós; Ricardo Weinlich; Vanderson Rocha (HemaSphere)
Abstract Sickle cell disease (SCD) is a monogenic disease, resulting from a single‐point mutation, that presents a complex pathophysiology and high clinical heterogeneity. Inflammation stands as a prominent characteristic of SCD. Over the past few decades, the role of different cells and molecules in the regulation of the inflammatory process has been elucidated. In conjunction with the polymerization of hemoglobin S (HbS), intravascular hemolysis, which releases free heme, HbS, and hemoglobin‐related damage‐associated molecular patterns, initiates multiple inflammatory pathways that are not yet fully comprehended. These complex phenomena lead to a vicious cycle that perpetuates vaso‐occlusion, hemolysis, and inflammation. To date, few inflammatory biomarkers can predict disease complications; conversely, there is a plethora of therapies that reduce inflammation in SCD, although clinical outcomes vary widely. Importantly, whether the clinical heterogeneity and complications are related to the degree of inflammation is not known. This review aims to further our understanding of the roles of main immune cells, and other inflammatory factors, as potential prognostic biomarkers for predicting clinical outcomes or identifying novel treatments for SCD.